Early invasive strategy in senior patients with non-ST-segment elevation myocardial infarction: is it cost-effective? - a decision-analytic model and value of information analysis - Luke Vale; Mehdi Javanbakht; Julija Simpson (BMJ Open)
Background Non-ST-elevation myocardial infarction (NSTEMI) is the most common type of heart attack in the UK and it is becoming increasingly prevalent among older people. An early invasive treatment strategy may be effective and cost-effective for treating NSTEMI but evidence is currently unclear.Objectives To assess the cost-effectiveness of the early invasive strategy versus medical management in elderly patients with NSTEMI and to provide guidance for future research in this area.Methods A long-term Markov state transition model was developed. Model inputs were systematically derived from a number of sources most appropriate to a UK relevant analysis, such as published studies and national routine data. Costs were estimated from the perspective of National Health Service and Personal Social Services. The model was developed using TreeAge Pro software. Based on a probabilistic sensitivity analysis, a value of information analysis was carried out to establish the value of decision uncertainty both overall and for specific input parameters.Results In 2017 UK £, the incremental cost-effectiveness ratio of the early invasive strategy was £46 916 for each additional quality-adjusted life-year (QALY) gained, with a probability of being cost-effective of 23% at a cost-effectiveness threshold of £20 000/QALY. There was a considerable decision uncertainty with these results. The value of removing all this uncertainty was up to £1 920 000 annually. Most uncertainty related to clinical effectiveness parameters and the optimal study design to remove this uncertainty would be a randomised controlled trial.Conclusion Based on current evidence, the early invasive strategy is not likely to be cost-effective for elderly patients with NSTEMI. This conclusion should be interpreted with caution mainly due to the absence of NSTEMI-specific data and long-term clinical effectiveness estimates.